Secretion of metalloendopeptidase 24.15 (EC 3.4.24.15) - Ferro, E. S.; Tullai, J. W.; Glucksman, M. J.; Roberts, J. L. (Mary Ann Liebert, Inc., 1999)
The metalloendopeptidase EP24.15 (EC3.4.24.15) is a neuropeptide-metabolizing enzyme present in neural and endocrine tissues, presumably functioning extracellularly, Because the majority of the EP24.15 activity is identified in the soluble fraction of cellular homogenates, suggesting that the enzyme is primarily an intracellular protein, we addressed the issue of how EP24.15 arrives in the extracellular environment, We utilized a model system of neuroendocrine secretion, the AtT20 cell, According to both enzymatic activity and immunologic assays, EP24.15 was synthesized in and released from AtT20 cells. Under basal conditions and after stimulation by corticotropin-releasing hormone or the calcium ionophore A23187, EP24.15 activity accumulated in the culture medium. This secretion was not attributable to cell damage, as judged by the absence of release of cytosolic enzyme markers and the ability to exclude trypan blue dye. Pulse-chase analysis and subcellular fractionation of AtT20 cell extracts suggested that the mechanism of EP24.15 secretion is not solely via classical secretory pathways, Additionally, drugs which disrupt the classical secretory pathway, such as Brefeldin A and nocodazole, blocked A23187-stimulated EP24.15 release yet had no effect on basal EP24.15 release, suggesting differences in the basal and stimulated pathways of secretion for EP24.15. In summary, EP24.15 appears to be secreted from AtT20 pituitary cells into the extracellular milieu, where the enzyme can participate in the physiologic metabolism of neuropeptides.